Global Versus Momentary Osteoarthritis Pain and Emotional Distress: Emotional Intelligence as Moderator. Issue 8 (3rd February 2018) - Parmelee, Patricia A; Scicolone, Monica A; Cox, Brian S; DeCaro, Jason A; Keefe, Francis J; Smith, Dylan M
Abstract : Attention to mood states exacerbates the experience of osteoarthritis pain both momentarily and in the long run. However, clarity of moods and the ability to maintain a positive mood help buffer the negative effects of pain on emotional well-being Abstract: Background: Pain and emotional well-being are complexly associated both globally and in the moment. Emotional regulation strategies may contribute to that complexity by shaping the pain–well-being association. Purpose: Using emotional intelligence (EI) as an integrative conceptual framework, this study probed the role of emotional regulation in the associations of osteoarthritis pain with emotional well-being in varying time frames. Perceived attention to, clarity, and regulation of emotions were examined as predictors of well-being, and as moderators of the well-being–pain association, at global and momentary (within-day) levels. Methods: In a microlongitudinal study, 218 older adults with physician-diagnosed knee osteoarthritis self-reported global pain, depressive symptoms, and EI (mood attention, clarity, and repair). Momentary pain and positive and negative affect were then assessed four times daily for 7 days. EI subscales were examined as moderators of the pain–well-being association at global and momentary levels, controlling demographics and general health. Results: Global and momentary pain were positively associated with mood clarity and negatively with attention, but not with repair. Clarity and repair negatively predicted depression, and buffered effects of pain on depression. Momentary negative affect was negatively predicted by mood clarity and repair; again, clarity and mood repair buffered effects of momentary pain on negative affect. Only mood repair predicted positive affect, with no interactions emerging. Conclusions: Attention to mood states exacerbates the experience of pain in both short and long terms. In contrast, both mood clarity and ability to repair moods appear important to both momentary and longer-term emotional well-being.